Clinical Analysis of Factors Influencing the Development of Placenta Praevia and Perinatal Outcomes in First-Time Pregnant Patients - Zhou, Chunhua; Zhao, Yang; Li, Yongmei (Frontiers in Surgery, 2022)
Objective To analyze the risk factors associated with the development of placenta praevia in first-time pregnant patients and to observe the perinatal clinical outcomes of patients. Methods The clinical data of 112 pregnant women with placenta praevia (PP group) and 224 pregnant women with normal placental position (general group) who delivered in our hospital from August 2016 to August 2021 were retrospectively analyzed. Baseline demographic data were collected from both groups, and logistic regression models were used to analyze the factors influencing the occurrence of placenta praevia in patients with first pregnancy. The perinatal outcomes of patients in the two groups were also counted and compared. Results Histories of endometriosis, use of assisted reproductive technology, and smoking or secondhand smoke inhalation were all high risk factors for placenta praevia in patients with first pregnancies, and the proportion of maternal and neonatal adverse outcomes was significantly higher in the PP group than in the general group (P < 0.05). Conclusion Histories of endometriosis, smoking (secondhand smoke), and use of assisted reproductive technologies are independent risk factors for placenta praevia in patients with first pregnancies.